Effect of peritoneal dialysis combined with hemodialysis on cardiovascular disease in patients with end stage renal disease - WEI Ming-ming; LI Su; ZHANG Shao-qing; QIAO Bai-lu; LI Xin-jian (Linchuang shenzangbing zazhi)
Objective To investigate the effect of peritoneal dialysis combined with hemodialysis（PHD） on the improvement of cardiovascular disease in patients with end-stage renal disease（ESRD）.Methods In this retrospective analysis,the clinical characteristics and outcomes of 14 patients with end-stage renal disease who comes from the department of internal medicine,Affiliated Hospital of lining Medical College in Shandong and had switched from PD alone to combined therapy with PHD were studied.The general status,clinical manifestations and nutritional status of the patients were followed up,and the biochemical indicator,parathyroid hormone,Carotid intima media thickness（CIMT）,β2-microglobulin（β2-MG）,systolic and diastolic blood pressure,left ventricular ejection fraction and B type natriuretic peptideCBNP) before and after treatment were analyzed.Results After the treatment of PHD,diet improve,nausea,vomiting and other gastrointestinal symptoms disappear,3patients who have repeatedly heart failure don’t occur heart failure after the treatment of PHD,pruritus and restless legs symptoms significantly reduced,serum phosphorus[（1.76 ± 0.41） mmol/L vs.（1.48±0.28） mmol/L,P>0.05]parathyroid hormone[（367.93 ± 166.66） ng/L vs.（237.07 ±76.21） ng/L,P<0.05],BNP[（1 521.7 ± 701.0） μg/L vs.（712.1 ± 535.0） μg/L,P<0.01]were significantly decreased,the left ventricular ejection fraction was increased[（49.7 ± 3.1）%vs.（52.2±1.8）%,P<0.05],the CMT[（1.65 ±0.36） mm vs.1.72±0.33) mm,P>0.05]had no obvious changes compared with pre-treatment Qmclusions PHD can relieve the clinical symptoms,improve the nutritional status of patients,reduce serum phosphorus and hyperparathyroidism,delay the progress of atherosclerosis,and it can as a new renal replacement treatment uses in clinical.